URBAN POLITICS KABUPATEN BENGKALIS (STUDI KEBIJAKAN BANTUAN PENDIDIKAN PEMERINTAH KABUPATEN BENGKALIS) - ", Adrius; Anwar, Khairul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Education is very supportive of a nation's progress , can be used as the main factor of tigkat the quality of the HR ( Human Resources ) in facing the challenges of the contemporary era . Bengkalis have natural resources of oil earth and crop that delivers the richest counties ranked number two in Indonesia after Kutai Kartanegara. With a large budget each year in excess of the rate of Rp 4 trillion be a tough task for the organizers of the region in allocating the budget post appropriate and not for corruption . Once a year the government budgeted cost of education aid as a flagship program of the Regent supporting Herliyan Saleh in improving the quality of human resources Bengkalis community . Theory proposed by Robert Dahl classifying policy analysis based actor and goals, organized interest groups and the interaction between actors and groups in the areas of policy, supported by Frieden in modern economic politics who observed the role of policy actor . This analysis also uses a decentralized approach in Indonesia , So the political criteria for urban / The Urban Politics exist on regional autonomy as stipulated in Law No. 32 of 2014 . The method used in this qualitative research , to obtain data based on interviews , observations and studies and then presented descriptively . Series of educational assistance policy Pemrintah Bengkalis very benyak terms of budget, but the target accuracy is still far from expectations. The involvement of non - governmental organizations that professional education is necessary in terms of policy formulation which is sometimes neglected by the government . Periodic disbursement , and the seriousness of the government apparatus needs to be improved. Keywords : Urban Politics , Decentralization , Education and Policy